PREDICTING PSYCHIATRIC OUTCOME FOLLOWING TEMPORAL LOBE EPILEPSY SURGERY: A LONGITUDINAL STUDY. Issue 9 (13th August 2015) - Pope, Rebecca Anne; Thompson, Pamela Jane; Rantell, Khadija; Stretton, Jason; Wright, Mary Anne; Foong, Jacqueline
Abstract : Objective: Neurosurgery is an effective therapy for selected individuals with medically refractory temporal lobe epilepsy (TLE). Following TLE surgery, however, affective symptoms (depression/anxiety) can worsen or develop for the first time (de novo), even in patients rendered seizure free. Predictors of psychiatric outcome have proved elusive and represent a current challenge in the practice of TLE surgery. We investigated whether indicators of more diffuse cerebral dysfunction are predictive of poorer psychiatric outcomes. Method: Forty-nine unilateral TLE surgical patients (25 RTLE; 24 LTLE) were assessed using the Beck Depression Inventory-Fast Screen (BDI-FS) and Beck Anxiety Inventory (BAI) preoperatively and 6 and 12 months postoperatively. All patients underwent neuropsychological assessments that included additional measures of executive function. Patients and family members also completed the Dysexecutive Questionnaire (DEX). A mixed-model repeated measures analysis was performed on each outcome (BDI-FS and BAI). Results: Preoperatively, 8 (16%) were mildly depressed, 2 (4%) were moderately depressed, and 6 (12%) reported severe depressive morbidity. Eighteen patients (37%) were mildly anxious, 6 (12%) were moderately anxious and 2 (4%) patients reported severe anxiety symptoms. We found that anxiety symptoms significantly improved within the first 6 months following TLE surgery, with no further improvement (i.e. between 6- and 12m follow-up). Depressive morbidity did not improve during the 12 month postoperative period. However, the magnitude and direction of mood change was significantly moderated by preoperative extra-temporal lobe dysfunction, with preoperative executive dysfunction indicators predicting increased depression and anxiety symptoms following surgery. There was no relationship between preoperative BDI-FS or BAI scores and seizure outcome (ILAE 1 vs 2–6) at 12 months (OR: 1.15, 95% CI: 0.84–1.56, p=0.38, OR: 1.04, 95% CI: 0.91–1.20, p=0.57, respectively), or change in affective morbidity and seizure outcome (BDI-FS: OR: 0.92, 95% CI: 0.76–1.10, p=0.34; BAI: OR: 0.84, 95% CI: 0.66–1.60, p=0.14). Conclusion: Pre-surgical cognitive and behavioural indices of executive dysfunction were predictive of poorer psychiatric outcome following TLE surgery. We found that anxiety symptoms improved in the early postoperative period, but depressive morbidity remained unchanged compared to preoperative levels. In addition, our findings have highlighted the clinical utility of the Dysexecutive Questionnaire (DEX-S). Examination of executive functioning in pre-surgical evaluations may lead to an increase in the power of prognostic models used to predict the psychiatric outcome of TLE surgery.